Assessment of pharmacokinetics-pharmacodynamics relationship of tropoxine in rats - V. P. Zherdev; G. B. Kolyvanov; A. A. Litvin; A. A. Novitskyi; T. S. Ganshina; A. A. Gorbunov; R. S. Mirzoyan (LLC "Publisher OKI", 2016)
ResuLts of precLinicaL pharmacodynamic and pharmacokinetic study of tropoxine (a new originaL antimigraine drug) after singLe intravenous administration in rats were presented. Tropoxine in significant extent suppresses constricting reactions of rat brain vesseLs, serotonin, and agonist of 5НТ2В/2С receptors. Direct reLationship between tropoxine concentrations decreasing in the rat bLood pLasma and changing of the brain circuLation associated with serotonin and m-chLorphenyLpiperazine.